STRATEGI PENGEMBANGAN POTENSI DAYA TARIK WISATA KAMPUNG ADAT PADANG RANAH KABUPATEN SIJUNJUNG - Gitra Putri Amelia; Khadijah Nurani (Jurnal Ekonomi dan Bisnis, 2023)
The background of the researchers choosing this title is that there is a problem of a lack of tourism development in the Sijunjung traditional village and a lack of potential for the attractiveness of the Sijunjung traditional village. This research aims to meknow what the strategy for developing tourist attractions in the village of Aday Padang, the realm of Sijunjung Regency. To find out what the potential and attractiveness of the Padang area traditional village of Sijunjung Regency is. This type of research uses field research and a qualitative descriptive approach. Techniques to collect data through observation, interviews and documentation. This research method uses SWOT analysis, IFE and EFE Matrix analysis, Cartesian diagrams, SWOT matrix analysis and score weight table analysis. Based on the research results obtained from internal (IFE) and external (EFE) evaluations using the SWOT matrix and score weight table, it was obtained that the highest total weight score was found in the S-T strategy, which was 3.25. This shows that the development of tourism potential must utilize the strengths possessed to reduce threats by 1) Maintaining the natural tourism potential of traditional villages so that no natural damage occurs. 2) Give a warning to those who exploit it so that the natural potential in traditional village tourist destinations is maintained. 3) Utilizing local culture, historical relics and natural potential in traditional villages to improve the image of Sijunjung Regency to be better known outside the region